Risk Analysis of PT XYZ E-Ticketing Information with Octave Method - Ade Kartika Dewi, Emil R.Kaburuan, Gresshinta, Hendrico Andre, Tuga Mauritsus (International Journal of Control and Automation, 2020)
The high demand of the community for Online Travel Agencies (OTA) services, PT XYZ as an airline and engaged in the sale of airplane tickets has developed a flight ticket sales program that has only been accessible via Desktop (DOS-based) into a WEB-based ticket sales program. By using Web Based Ticketing, the company can spread its wings by inviting agent agents in Indonesia to sell plane / hotel tickets with the Web that has been provided by the company. Ticket sales agent partners throughout Indonesia can use the PT XYZ Ticket Web portal to process flight and hotel ticket reservations. This web based IS / IT application aims to improve customer service, accuracy, speed that is in line with the company's Vision and Mission. But this must be accompanied by efforts to protect these IS / IT Assets from Risks.One of the risks that may arise in the future is the risk of corporate information security, where information becomes an important matter and is protected from unauthorized outsiders who may be misused for certain interests and damage the information. Information is an important asset of the company which must be protected and secured.